Use of endoscopic ultrasound-based techniques in tumor of the guts and beyond - Pei, Chu; Zeng, Guangqiao (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Endoscopic techniques in gastroenterology have been developing rapidly over the past two decades. Advances in minimally invasive endoscopic techniques allow for the detection and treatment of more gastrointestinal (GI) diseases than ever. In a manner of speaking, the advent of miniature ultrasound device coupled with endoscopy further shapes up a new epoch of intraluminal exploration. Today, endoscopic ultrasound (EUS) detection is indicated for study of a wider-ranging conditions within the GI wall, and even going beyond the latter, applicable to the organs surrounding the GI tract (1), including the lung, pancreas, gallbladder, liver, adrenal glands, bladder, and uterus.